Pembentukan Kerohanian Reformed: Sebuah Pendekatan secara Konfesi, Oikumenis, dan Teologis - Audy Santoso (STT Reformed Injili Internasional, 2023)
Spiritual formation as a practical subject in a Christian's life is often not thought reflectively, if not altogether ignored, even by those who claim within the Reformed tradition. This paper argues for the uniqueness of Christianity's spiritual formation from the other Abrahamic religions based on scriptural arguments and religious-social phenomena. The Reformation contributed to Christian spiritual formation based on general principles and Calvin's anthropological insights. The article concludes that Christian spiritual formation is none other than living a Triune life, that is, to be Christ-formed and Spirit-filled in our lives as children of God.